2001
DOI: 10.1006/lich.2000.0303
|View full text |Cite
|
Sign up to set email alerts
|

Broad Spectrum Antifungal Properties of the Lichen Heterodermia leucomela

Abstract: Broad spectrum antifungal properties of the lichen Heterodermia leucomela Lichens produce a diverse range of chemical products, many of which have been found to have antimicrobial activity (Elix 1996; Lawrey 1986; Land & Lundstrom 1998). Most of these antimicrobial substances are phenolic derivatives (e.g. usnic acid) and have extremely low solubilities in water. This short communication deals with the evaluation of water-soluble substances from Heterodermia leucomela (L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 4 publications
0
35
0
1
Order By: Relevance
“…Established results on the antifungal activity of Everniastrum cirrhatum with minimum fungicidal concentration (MFC) of as low as 60  μ L/mL against human pathogenic fungi (dermatophytes), namely, Epidermophyton floccosum, Microsporum gypseum, M. canis, M. audounii, Trichophyton rubrum, T. mentagrophytes, T. violaceum, and T. tonsurans, have also been reported in the past [33]. Heterodermia leucomelos was also found effective against human as well as plant pathogenic fungi [34]. Some macrolichens extracts, namely, Parmelia tinctorum, Ramalina sp., Teloschistes flavicans, and Usnea undulata , were tested and found effective against some pathogenic fungi [35].…”
Section: Resultsmentioning
confidence: 99%
“…Established results on the antifungal activity of Everniastrum cirrhatum with minimum fungicidal concentration (MFC) of as low as 60  μ L/mL against human pathogenic fungi (dermatophytes), namely, Epidermophyton floccosum, Microsporum gypseum, M. canis, M. audounii, Trichophyton rubrum, T. mentagrophytes, T. violaceum, and T. tonsurans, have also been reported in the past [33]. Heterodermia leucomelos was also found effective against human as well as plant pathogenic fungi [34]. Some macrolichens extracts, namely, Parmelia tinctorum, Ramalina sp., Teloschistes flavicans, and Usnea undulata , were tested and found effective against some pathogenic fungi [35].…”
Section: Resultsmentioning
confidence: 99%
“…Fungal diseases of plants result in decreased [ [42][43][44][45][46][47][48] In this study, we evaluated antifungal potential of two concentrations of an extract of H. incana, viz., 0.5 mg/ml and 1 mg/ml by poisoned food technique. Poisoning of medium with extract resulted in drastic reduction in mycelial growth of test fungi [ Table 3 and Figure 3].…”
Section: Antibacterial Activity Of H Incanamentioning
confidence: 99%
“…was 78.26%, 76.60%, and 68.77%, respectively [ Figure 4]. Earlier studies have shown the potential of some Heterodermia species such as H. boryi, [15] H. diademata, [36,49] H. comosa, [50] H. leucomelos, [42,51] H. microphylla, [43] and H. obscurata [8] to inhibit phytopathogenic fungi.…”
Section: Antibacterial Activity Of H Incanamentioning
confidence: 99%
“…Otro hongo liquenizado con una marcada actividad fungicida fue Parmelia sulcata, que en dosis bajas (0,0037 mg/ml), inhibió el crecimiento de Fusarium oxysporum, Botritis cinérea y Aspergillus fumigatus (Rankovic y Kosanic, 2012). Por otra parte, Shahi et al (2001) utilizaron el extracto acuoso de Heterodermia leucomela obteniendo efecto de un 100% de inhibición a dosis de 60 y 80 µl/ml, sobre los hongos fitopatógenos Cladosporium gladosporioides, Curvularia lunata y Fusarium oxysporum. Los resultados obtenidos en la clasificación de los extractos liquénicos sobre P. nicotianae y R. solani pueden variar de acuerdo a las dosis establecidas para el estudio, por lo que se podrían analizar con otras concentraciones mayores.…”
Section: Porcentajes De Inhibición Del Crecimiento Micelialunclassified